A Content Analysis of the Journal of Applied Sport Management from 2009 to 2024 - Jeffrey Petersen; Marshall Magnusen (Journal of Applied Sports Management, 2025)
The Journal of Applied Sport Management (JASM), originally launched as the Journal of Sport Administration and Supervision in 2009, has published a total of 231 peer-reviewed manuscripts during its first 16 years. While many other journals within this field have been studied to better understand research topics, types, and impact, JASM has yet to be examined. This content analysis study explored 19 variables related to the research topics, methods, authorship, and impact of these articles, and provided important insights from both descriptive and inferential statistics regarding existing trends and opportunities for development for both the journal as a whole and its contributing scholars.
Keywords: academic journal; authorship; impact; methodology; review